Analisis Sosiologi Sastra Pada Lagu - Sahri Nova Yoga; Farida Isroani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Songs are a form of literary work. This is in accordance with the opinion of Sugono (2008:77) who states that, "Songs are a variety of rhythmic sounds (talking, singing, reading, etc.)." Songs are artistic changes in tones or sounds in sequences, combinations and temporal relationships (usually accompanied by musical instruments) to produce musical changes that are unified and continuous (contain rhythm). This variety of rhythmic tones or sounds is called a song.